Father-child attachment on children's screen time: mediating role of ego resilience - Hwa-Mi Yang; Hye-Ryoung Kim (BMC, 2024)
Abstract Background Children spend a significant amount of time engaging in sedentary behaviors, defined as activities that do not increase energy expenditure significantly above resting levels, such as watching TV and playing PC/video games. Increased screen time is a significant public health concern because children are in a developmental stage where lifestyle behaviors predict various health outcomes in adulthood and beyond. This study explores the links between parent-child attachment, ego resilience, and children's screen time. Methods This cross-sectional correlation study uses 1,163 parents and their children data from the 12th Panel Survey of Korean Children. The study instruments were a modified Armsden and Greenberg scale of parent-child attachment and modified the children's ego resilience scale of the Block and Kremen. Children's screen time was classified as more than 2 h per day spent watching television, playing on computers, or playing video games in their leisure time. Results Study results show a negative association between father-child attachment and children's screen time (ß = -0.43, p < .001) and a positive association between father-child attachment and ego resilience (ß = 0.24, p < .001). Ego resilience showed a negative link to children's screen time after adjusting for parental attachment (ß =- 0.03, p = .009). Father-child attachment link to children's screen time (ß = -0.36, p < .001) continued even though the association was slightly reduced in magnitude after adjusting for ego resilience. Conclusions Our findings show the mediating role of ego resilience on a negative path of father-child attachment to children's screen time. This finding emphasizes the importance of fostering solid father-child relationships and enhancing children's psychological resilience as critical strategies for reducing excessive screen time. By addressing emotional support and resilience-building, interventions can more effectively promote healthier behavioral outcomes in children.